Pengaruh Ekstrak Buah Honje terhadap Berat Badan Mencit Jantan - Zico Fakhrur Rozi; Endang; Rama; Vincent Wijaya; Nugroho (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effect of honje fruit (Etlingera hemisphaerica) extract on the body weight of male mice (Mus musculus). The method used was an experimental study with a Completely Randomized Design (CRD). A total of 25 male mice were divided into five groups consisting of one control group and four treatment groups receiving extract doses of 0.13 mg/kgBW, 0.26 mg/kgBW, 0.38 mg/kgBW, and 0.52 mg/kgBW for 10 days. Data were analyzed using the Shapiro–Wilk normality test, homogeneity test, and ANOVA. The results showed that the data were normally distributed and homogeneous, and there was no significant difference in mean body weight among treatment groups. In conclusion, administration of honje fruit extract at various doses does not significantly affect the body weight of male mice during the treatment period. Keywords: Body Weight, Honje Fruit Extract, Male Mice.